Potensi Tepung Biji Kecipir (Psophocarpus tetragonolobus) sebagai Bahan Alternatif Sumber Nitrogen dalam Media Mannitol Salt Agar (MSA) untuk Pertumbuhan Staphylococcus aureus - Urip, Urip; Pratiwi, Nanda Yuniza; Tatontos, Erlin Yustin; Diarti, Maruni Wiwin (Bioscientist : Jurnal Ilmiah Biologi, 2022)
The purpose of this study was to determine the potential of winged bean (Psophocarpus tetragonolobus) seed powder as an alternative medium for Mannitol Salt Agar (MSA) against the growth of Staphylococcus aureus bacteria. This research method is true experiment with Completely Randomized Design (CRD). The experimental unit of this research was winged bean seed flour and Staphylococcus aureus. Winged bean seed flour used with 5 treatments, namely 2 gr, 4 gr, 6 gr, 8 gr, and 10 gr with each replication 5 times. The results showed that the standard MSA as a control showed an average of 3211 colonies, the average colony at a concentration of 2% was 372 colonies, the average colony on a 4% concentration plate was 419 colonies, the average colony on a 6% concentration plate was 544 colonies, the average colony on an 8% concentration plate were 622 colonies, and the average colony on a 10% concentration plate was 816 colonies. The conclusion of this study is winged bean seed powder has the potential as an alternative source of nitrogen in Mannitol Salt Agar (MSA) media for the growth of Staphylococcus aureus.